Asvatantra. (24th March 2023) - Chebrol, Madhulika
Abstract : Traditionally considered timeless and static, dharma is necessarily rooted in the customs of people and, therefore, a function of changing times and beliefs. The purpose of this paper is to analyse how medieval Brahmanical scholars understood, justified, and interpreted dharma within the scholastic tradition and whether it was possible to reinterpret various prescriptive rules to suit the social milieu of their times. These reinterpretations, if they can be sufficiently attested through scholarship, must have their roots in historical realities. Whether the tradition wishes to accommodate change or resist it, scholarly readings and commentaries provide a valuable insight into how law was read and interpreted by the Brahmanical scholastic tradition. This paper studies the dharmic norms relating to the dependence (asvatantrya) of women as interpreted by the tenth-century commentator Medhatithi, writing on the Manavadharmasastra. Medhatithi's lengthy commentary on controversial points suggests a vibrant scholastic debate in which interpretations varied and certain historical realities had been taken into account.